Reflections on the challenges and opportunities for palliative care in Nepal - Daniel Munday; Ruth Powys (Health for All Nations, 2017)
Palliative care in Nepal has been developing over the last 20 years, led by pioneering doctors and nurses who have gained experience in the specialty, often while working overseas, or who have had the opportunity to do clinical attachments abroad. Recently, in collaboration with international palliative care specialists, a national strategy has been developed and adopted to guide future development so that palliative care for all who need it can be provided. This article explores the faith-based context for palliative care and describes the particular issues Nepal faces, the work of Christian mission organizations in supporting palliative care development, and the need for religious and cultural sensitivity.